OPTIMALISASI MEDIASI DAN ARBITRASE SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA ANTARA TENAGA MEDIS DAN PASIEN BERDASARKAN UU NO. 17 TAHUN 2023 TENTANG KESEHATAN - Gunawan Widjaja (Adiba Aisha Amira, 2025)
The implementation of mediation and arbitration as alternative dispute resolution in Indonesia faces various complex challenges, ranging from low compliance with arbitration awards, lack of public understanding, to limited human resources and supporting infrastructure. These obstacles have resulted in the effectiveness of mediation and arbitration being less than optimal and still less popular than dispute resolution through the courts. This article examines these challenges and offers solutions in the form of improved education, strengthened regulations, development of mediator and arbitrator competencies, and effective use of technology. With these strategic steps, it is hoped that mediation and arbitration can become the primary choice for resolving disputes quickly, cheaply, and fairly in Indonesia.